The Flipped-Classroom Instructional Procedure Development and Its Implementation Effectiveness in Improving Procedural Knowledge Learning Outcomes at Vocational High Schools - Herlambang, Admaja Dwi; Fransisca, Olivia Dyah; Afirianto, Tri (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2023)
The students' number limitation in a classroom and the compression of face-to-face time challenge teachers to present practical learning scenarios to achieve learning objectives. This study aims to develop student learning procedures with the flipped classroom (FC) instructional model and determine its use in improving student learning outcomes. The research was conducted at a public information technology vocational high school in Malang, East Java Province, Indonesia. The FC instructional procedure development approach is based on the ADDIE (analysis, design, development, implementation, and evaluation) phase. The FC instructional procedure was developed in conjunction with a constructivist instructional strategy, consisting of five primary stages: (1) perception, (2) exploration, (3) restructuring, (4) implementation, and (5) review and evaluation. FC instructional procedure effectiveness was tested using the Randomized Pre-test and Post-test Control Group Design research design. The control and experimental groups consist of 30 students with randomization. The research found that the learning outcomes of the experimental group (EGLO = 70.00) were greater than those of the control group (CGLO = 64.30). The normalized gain index of the experimental groups (g = 0.50) was more significant than the control groups (g = 0.41). The conclusion is that the FC procedures with a constructivist approach have proven more effective in improving student learning outcomes.